2017
DOI: 10.1021/jacs.7b07748
|View full text |Cite
|
Sign up to set email alerts
|

A Photoactivatable Probe for Super-Resolution Imaging of Enzymatic Activity in Live Cells

Abstract: A dual-activatable, fluorogenic probe was developed to sense esterase activity with single-molecule resolution. Without enzymatic pre-activation, the diazoindanone-based probe has an electron-poor core and, upon irradiation, undergoes Wolff rearrangement to give a ring-expanded xanthene core that is nonemissive. If the probe is pre-activated by carboxylesterases, the tricyclic core becomes electron-rich, and the photoinduced Wolff rearrangement produces a highly emissive rhodol dye. Live-cell and solution stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 33 publications
(56 reference statements)
0
80
0
3
Order By: Relevance
“…Upon irradiation, the diazoindanone would undergo Wolff rearrangement to give a brightly fluorescent rhodamine dye. [10,11] We studied the photophysical properties of ER-1 using absorption and fluorescence spectroscopy (Figure 1,a) in phosphate buffered saline (PBS, pH = 7.4) and measured an approximate 150-fold increase in fluorescence emission after 15 min of irradiation (405 nm, 2 mW cm À 2 , 10 min). The emission signal appeared to reach saturation after 15 min of irradiation under these same conditions (Figure 1,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon irradiation, the diazoindanone would undergo Wolff rearrangement to give a brightly fluorescent rhodamine dye. [10,11] We studied the photophysical properties of ER-1 using absorption and fluorescence spectroscopy (Figure 1,a) in phosphate buffered saline (PBS, pH = 7.4) and measured an approximate 150-fold increase in fluorescence emission after 15 min of irradiation (405 nm, 2 mW cm À 2 , 10 min). The emission signal appeared to reach saturation after 15 min of irradiation under these same conditions (Figure 1,b).…”
Section: Resultsmentioning
confidence: 99%
“…We reported the use of diazoindanone rhodols as effective dual photoactivatable dyes that emit a fluorescent signal selectively in the presence of an active carboxylesterase. [11] This method enables the detection of clusters of active enzymes because the photoactivated dyes form a covalent bond with their surroundings, which limits their diffusion and facilitates SMLM.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the identity of the putative photoproduct, we prepared compound 3 ( Figure 1C), which we expected to be the major photoproduct. [8,15,16] Liquid chromatography coupled with mass spectrometry (LC-MS) confirmed that compound 3 is indeed the major photoproduct formed upon irradiation of 2 in water ( Figure S5). Thesame results were obtained when compound 2 was irradiated with 405 nm light, which is commonly used in fluorescence microscopy ( Figure S6).…”
mentioning
confidence: 90%
“…Even though super-resolution microscopy techniques such as stochastic optical reconstruction microscopy (STORM) [6] and photoactivation localization microscopy (PALM) [7] are well established, there is al ack of fluorescent sensors that are specifically optimized for these techniques.W er ecently developed as ensing mechanism that is compatible with STORM. [8] We reported that photoactivatable diazoindanone-modified xanthene dyes bearing electron-withdrawing substituents mainly form nonfluorescent photoproducts upon irradiation. Photoactivation following enzymatic transformation of the substituent into an electron-donating group yields highly fluorescent photoproducts that display minimal diffusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation